Socio-Economic and Political Dimensions of Christian and Muslim Pilgrimages in Lagos State, Nigeria (2012)
Existing studies on pilgrimage have focused more on the spiritual dimension and have neglected the social, economic and political aspects. For instance, the activities of stakeholders such as state governments, pilgrims, retailers, bureau de change officers, and pilgrimage board officials are hardly explored from a holistic point of view, thus allowing for an abbreviated conception of pilgrimage. This study, therefore, examined the practice of pilgrimage in Lagos with a view to determining its socio-economic and political dimensions and how these interface with the ethos of Christian and Muslim pilgrimage. The study adopted Durkheim‘s functional theory, which describes religion as an institutional tool that influences behaviour of individuals and groups positively and negatively. The Pilgrimage Centres both in Lagos State Secretariat, Alausa and Local Airport, Ikeja were purposively selected as study locations. Qualitative data were obtained through observation and the interview of 50 informants randomly selected from a population of Christian and Muslim pilgrims, retailers of pilgrim souvenirs, officials of pilgrimage board, and bureau de change operators. Furthermore, six focus group discussions were held with 70 Christian and Muslim pilgrims. Data collected were subjected to content analysis. Majority of Christian and Muslim performing pilgrimages from Lagos State were state-sponsored and for the purpose of which the state expended between five and seven billion naira annually. Pilgrimage sponsorship constituted an aspect of patronage politics, as sponsored pilgrims were basically government officials and their spouses, senior civil servants, party faithful, clerics and others whose loyalty to the ruling party was being rewarded. or whose influences were adjudged crucial to achieving electoral successes in future. The Lagos State Government considered sponsorship of pilgrimages as a form of social responsibility, which has helped to foster inter-religious ties and cooperation among the two major religious groups in the State. Pilgrimage periods were equally boom time for businesses connected with the exercise, especially travel agencies and bureau de change operators, majority of whom claimed that the demand for foreign exchange doubled during pilgrimage seasons. In addition, some pilgrims, mostly women, utilised pilgrimage trips to shop for trade articles like jewelleries and items considered cheaper in the holy lands. Social activities like public feasting and wearing of common attire created cordial relationship among pilgrims and facilitated the development of new identity and social networks. Many pilgrims also embarked upon the exercise to enhance their upward social mobility, most especially as the titles of Alhaji/Alhaja and JP were widely seen as capable of conferring the bearers with statuses that could be deployed to advantage. The socio-economic and political dimensions of Christian and Muslim pilgrimage exercises were indicative of much emphasis on other mundane interests other than religious activities. This suggested the invasion of the religious domain by global materialism. For religious pilgrimages to retain their relevance and move beyond mere tourism, the basic rationale for the exercises, especially the aspects of piety and convenience, should be re-examined to ensure that ethics of the pilgrimage is preserved